The feasibility of an interactive voice response system (IVRS) for monitoring patient safety after discharge from the ED. Issue 3 (24th November 2017) - Calder, Lisa A; Cwinn, A Adam; Gatien, Mathieu; Gee, Andrew; Larocque, Natasha; Calder-Sprackman, Samantha; De Gorter, Ria; Zlepnig, Jennifer; Stiell, Ian G; Forster, Alan J
Abstract : Background: Return ED visits are frequent and may be due to adverse events: adverse outcomes related to healthcare received. An interactive voice response system (IVRS) is a technology that translates human telephone input into digital data. Use of IVRS has been explored in many healthcare settings but to a limited extent in the ED. We determined the feasibility of using an IVRS to assess for adverse events after ED discharge. Methods: This before and after study assessed detection of adverse events among consecutive high-acuity patients discharged from a tertiary care ED pre-IVRS and post-IVRS over two 2-week periods. The IVRS asked if the patient was having a health problem and if they wanted to speak to a nurse. Patients responding yes received a telephone interview. We searched health records for deaths, admissions to hospital and return ED visits. Three trained emergency physicians independently determined adverse event occurrence. We analysed the data using descriptive statistics. Results: Of 968 patients studied, patients' age, sex, acuity and presenting complaint were comparable pre-IVRS and post-IVRS. Postimplementation, 393 (81.7%) of 481 patients had successful IVRS contact. Of these, 89 (22.6%) wanted to speak to a nurse. A total of 37 adverse events were detected over the two periods: 10 patients with 10 (6.5%) adverse events pre-IVRS and 16 patients with 27 (16.9%) adverse events post-IVRS. In the postimplementation period, the adverse events of seven patients were detected by the IVRS and five patients spontaneously requested assistance navigating post-ED care. Conclusions: This was a successful proof-of-concept study for applying IVRS technology to assess patient safety issues for discharged high-acuity ED patients.